Product space V2x V2 and plane fronted waves in general projective relativity - Singh T.; Singh G.P. (My University, 2025)
In this paper the field equations of General Projective Relativity have been investigated in the product space of V2x V2 space-time (Bertotti, 1959) and plane fronted metric of Peres (1959). It is shown that wave solutions exist in both space-times. In Peres' space we mention two solutions which can be interpreted as plane-monochromatic waves and wave packets, respectively. © 1989 Kluwer Academic Publishers.